Efficacy of Smart City Data Layers in virtual reality for emergency evacuation behaviours - Reinout Wiltenburg; William Hurst; Frida Ruiz Mendoza; Caspar Krampe; Bedir Tekinerdogan (Array, 2025)
Virtual reality is increasingly finding a footing within a range of movement-based studies for different fire emergency settings. Compared to real-world experiments, the core advantage of a virtual reality approach is the safe experiment process and the possibility of creating bespoke and flexible solutions for both testing and training scenarios of smart city buildings. Additionally, virtual reality environments cater for the integration of various layers of information relating to evacuation protocols within digitally recreated public buildings; thus, enabling studies on understanding how the role of extra information can support decision-making when evacuating a building. One way of presenting this information is by employing the Smart City Data Layers which has yet to be investigated, thus, in this study, a Smart City Data Layer-enhanced virtual reality environment is presented. The environment is set up to provide extra information for the participants on how to escape the building provided and, with a control environment providing no additional information for the participants. The behavioural analysis showed that the Smart City Data Layer led to longer time and distance behaviour during the escape in two out of three escape scenarios. The result shows how crucial the design is, and the amount of information presented. For example, findings indicate that too much information leads to potential information overload. In addition, nausea and dizziness were found to be significant variables (p = 0.001, t = −3.611 and p = 0.006, t = −2.965) influencing the time and distance for escape when tested in this environment. Despite the contradictory results, 71 % of the 34 participants found the VR technology very helpful in visualising green outlines for doors during the escape. However, the results suggest that the inclusion of the Smart City Data Layer may lead to overconfidence, resulting in a longer evacuation time.